PELAKSANAAN PROMOSI MELALUI MEDIA CETAK BROSUR PADA OBYEK WISATA BALAI KERAPATAN TINGGI KABUPATEN SIAK - Sahara, Siti Fitrah; Arief, Andi M. Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Siak Sri Indrapura has tourism potencial as nature tourism, cultural tourism, religious tourism and history tourism. Therefore, this research was conducted to find out the implementation of promotion trough media brochure by Dinas Pariwisata Kabupaten Siak to attract tourists coming to Balai Kerapatan Tinggi of Siak Sri Indrapura.The reseacrh aims to find out how responses the implementation of promotion through media brochure in Balai Kerapatan tinggi, Kabupaten Siak. This research used a descriptive quantitative method to examine problems in the lift. The samples in this study were 75 respondents, who were taken by using simpel random sampling. While data collection techniques in this study using observation, interview, questioner, and document. By using a Likert scale as a measure to determine the length of the short interval. From the results of research that’s been done, the result is the implementation of promotion through media brochure in Balai Kerapatan Tinggi less satisfying.Keywords: Promotion Mix, The Promotion of Media Brochure